Donor-acceptor couples and late transition metal complexes of oxidation-labile 1,4,5,8-tetrakis(guanidino)naphthalene superbases - Vitske, Viktoriia; Roquette, Pascal; Leingang, Simone; Adam, Christian; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
In this manuscript the reactivity of the two oxidation-labile superbases 1,4,5,8-tetrakis(N,N,N′,N′-tetramethylguanidino)naphthalene and the newly synthesized 1,4,5,8-tetrakis(N,N′-dimethyl-N,N′-ethylene-guanidino)naphthalene(tdmegn) are discussed and compared with that of related organic electron donors. The work includes oxidation with inorganic and organic oxidation reagents, as well as the preparation and characterization of dinuclear CoII, NiII and CuI complexes. Magnetic coupling in the dinuclear CoII and NiII complexes is studied on the basis of SQUID measurements. Finally, the results of experiments on the oxidation of the dinuclear CuI complexes are presented.
Gesehen am 08.12.2022